Implementation Learning Through Media Audiovisual to Enhance Interest Student Learning on Social Sciences Subject in Class VIII of MTs Al Khairaat Kalukubula - Nurfadhila, Yusmi; Prasetyawati, Priyatna; Juraid; Windayanti (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aims to: (1) Describe Social Science explains how effective the application of audiovisual media is in increase students' interest in learning MTs Al Khairaat Kalukubula, (2) defines the factors that influence students' interest in using audiovisual media in Social Sciences learning in Class VIII, and (3) identifies the obstacles faced in implementing audiovisual media. The method used in this research is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The data processing process is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of audiovisual media has a positive impact on students' learning interest, which is seen from the increase in their interest, attention, and activeness during the learning process. And there are main factors in the success of this audiovisual media, namely attractive visual and audio displays, the suitability of the material with the video, learning interactivity, support from teachers who actively explain, and a conducive classroom environment. There are also several obstacles faced in the implementation of this media, including limited facilities, technical problems, and inadequate video duration. To overcome these obstacles, teachers make preparations early before learning, choose videos that are more appropriate for learning time, and coordinate with the school regarding the availability of facilities.